Implementation of Fairness Theory in Minimum Wages Policy for Small and Medium Enterprise in Indonesia - Sugeng Prayitno; Irma Rachmawati Ma’ruf; Budi Drajat Budiman (GoAcademica Research & Publishing, 2020)
Wage Minimum always gives disparity in political power and lawmaker since it is tough to describe how to determine individual wages. For this reason, the wage minimum is a dilemma for workers and employers. Fairness conception for wage minimum is a solution to this problem. The fairness conception will guide the wage minimum to the supreme law. Although there are so many regulations concerning wage minimum, there are still many problems that arise, including break the law of wage minimum. The rules must consider the balance of interest between workers and employers to reduce disobedience of minimum wage.